Admissions guide to American Colleges for international students - DOLAN, Andrew ([Tidak Terdaftar], 2011)
This book shows international students how to apply for admission to undergraduate colleges in the United States. It tells where to find out the SAT®, ACT® and TOEFL® scores needed to get admitted to American colleges from print and online directories, and how to avoid common mistakes on college admission essays. It explains where to get information about financial aid for international students, and how to obtain detailed inside information about individual colleges that is not available from college directories and web sites. This book shows how to apply to multiple American colleges using a common application, and how to transfer into four-year colleges and universities. This book tells international students what to do while studying in American undergraduate schools to improve their chances of admission to selective American graduate schools, and includes the web sites of over a hundred major American colleges.